Insight into the Cycling Behaviour of Metal Anodes, Enabled by X‐ray Tomography and Mathematical Modelling. Issue 9 (27th January 2022) - Rossi, Francesca; Mancini, Lucia; Sgura, Ivonne; Boniardi, Marco; Casaroli, Andrea; Kao, Alexander Peter; Bozzini, Benedetto
Abstract: This work tackles the methodological challenge of rationalizing symmetric‐cell cycling data from a materials‐science perspective, through experiment replication, mathematical modelling, and tomographic imaging. Specifically, we address Zn electrode cycling in alkaline electrolyte with and without adding tetrabutylammonium bromide (TBAB). This additive is known from literature, but its practical impact is jeopardized by lack of in‐depth understanding of its behaviour. Electrochemical testing was carried out at practically relevant current densities and the effect of variations of operating conditions was taken into account. The physical chemistry underlying cell potential profiles, has been modelled mathematically, accounting for: electrokinetics, mass‐transport, electrode shape change and passivation. In particular, we disclosed an unexpected joint effect of TBAB and current density on passivation time: tomography allowed to rationalise this behaviour in terms of precipitate morphology. Abstract : Symmetric Zn cell cycling shows that the effect of tetrabutylammonium bromide (TBAB) depends on current density. At 1 mA cm −2 TBAB notably increases time to passivation, but at 10 mA cm −2 it halves the cell lifespan. Electrochemical behaviour correlates clearly with the morphology of passivating precipitates, as disclosed by tomography.